CENTRAL VENOUS CATHETER-ASSOCIATED SEPSIS: A REVIEW OF THE LITERATURE - Carlos da Silva, Roberto; Evelly da Silva Olanda, Débora; Tatiane Freire, Wilma; Dayana da Silva Santos, Lady; da Silva Santos, Samara; Quitéria Fernandes Ferreira, Ana; Martins de Araújo, Núbia; Kelly da Silva, Nathalia; Gomes da Silva, William; Michele de Araújo Pedro, Fabiana; Herminio Falcão Torres, Geane; Ellen Costa Vasconcelos, Eduarda; et al. (Health and Society, 2023)
Objective: To understand the role of nurses in preventing bloodstream related infections with a focus on central venous catheters in ICU patients. Method: This is an integrative review in the following databases: Scielo, Biblioteca Virtual em Saúde, LILACS, as well as Google Acadêmico. The publications were carefully selected and separated in a table with the following descriptions to be filled in: Title, Author and Year; Results: The intensive care unit known as ICU, is located within hospitals and is responsible for providing intensified assistance to patients, using extreme measures, such as medications and invasive devices, such as venous catheters. The professional nurse contributes greatly to this service, minimizing the risk of infection in patients, in a careful and aseptic way. Conclusion: It was observed that the role of the nursing team is extremely important, since there are many risk factors for the development of infections. The institutions need to develop protocols, in addition to carrying out continuing education programs, promoting events with lectures, making the nursing team increasingly aware.